Leucocyte response and anti-inflammatory cytokines in community acquired pneumonia. Issue 2 (1st February 2001) - Kolling, U K; Hansen, F; Braun, J; Rink, L; Katus, H A; Dalhoff, K
Abstract : BACKGROUND: In the host defence of the lung neutrophils (PMN) play a central role. Apart from antimicrobial properties, recent data indicate that PMN also exert anti-inflammatory effects by stimulation and release of cytokine antagonists such as interleukin-1 receptor antagonist (IL-1ra). METHODS: Cytokine release from lipopolysaccharide stimulated whole blood was studied in 18 patients with community acquired pneumonia (CAP) and severe co-morbidities at admission and after 24 hours. Release of IL-1ra, interleukin-1β (IL-1β), tumour necrosis factor α (TNFα), soluble TNF receptor type I (sTNF-RI), and IL-8 was determined by ELISA. RESULTS: The mean (SD) leucocyte level at admission was 12.5 (4.1)/nl. There was a significant correlation between the release of anti-inflammatory cytokines such as IL-1ra and sTNF-RI and the leucocyte count at admission and after 24 hours. Additional in vitro experiments showed that co-incubation of peripheral blood mononuclear cells with autologous PMN led to a marked dose dependent increase in IL-1ra and sTNF-RI release. CONCLUSION: These results indicate that PMN may be responsible for the increase in anti-inflammatory cytokines in CAP. Strategies to increase neutrophil counts may exert beneficial effects, not only by augmenting the antimicrobial activity but also by modulating the inflammatory cytokine response.